Antibacterial, Antifungal, and Antidiabetic Effects of Leaf Extracts from Persea americana Mill. (Lauraceae). (11th November 2020) - Makopa, Mercy; Mangiza, Benjamin; Banda, Benjamin; Mozirandi, Winnie; Mombeshora, Molly; Mukanganyama, Stanley
Abstract : Fruits and leaves of Persia americana are used in traditional medical practices. This study was carried out to determine the antibacterial, antifungal, and antidiabetic effects of the leaf extracts from P. americana . The antibacterial activities of the leaf extracts were evaluated against Klebsiella pneumoniae and Staphylococcus epidermidis while antifungal activities were determined against Candida albicans and Candida tropicalis . The antidiabetic potential of the extracts was determined against mammalian α -glucosidase in vitro. The broth microdilution method was used to investigate the antibacterial and antifungal susceptibility of the microbial strains towards the leaf extracts. S. epidermidis was the most susceptible microbe out of the tested microorganisms. The acetone extract was the most potent extract against S. epidermidis with a minimum inhibitory concentration (MIC) of 50 μ g/mL. At 100 μ g/mL, the ethanol:water extract 18% of K. pneumoniae cells remained viable. Cell viability after exposure to the dichloromethane (DCM) and methanol extracts was 28% against C. albicans and 8% against C. tropicalis, respectively. The DCM:methanol and acetone extracts caused membrane damage in S. epidermidis exhibited by protein leakage. Only the acetone extract effected nucleic acid leakage. Screening of extracts' potential to inhibit the activity of α -glucosidase was carried out spectrophotometrically following the production of p-nitrophenol from p-nitrophenol-glucopyranoside (substrate) at a wavelength of 405 nm. Out of all the tested extracts, the methanolic extract showed the best inhibitory activity on α -glucosidase enzyme in a time-dependent and dose-dependent manner. K i and K inact values were found to be 1.4 mg/mL and 2.4 U/min, respectively, after incubation for 1 hour. It was concluded that the leaf extracts of P. americana contain phytochemicals with antibacterial, antifungal, and α -glucosidase inhibitory effects. Further studies are required for the identification of the active compounds in the leaf extracts responsible for these observed effects.